The conserved role of Krox-20 in directing Hox gene expression during vertebrate hindbrain segmentation. - Nonchev, S (1996)
Transient segmentation in the hindbrain is a fundamental morphogenetic phenomenon in the vertebrate embryo, and the restricted expression of subsets of Hox genes in the developing rhombomeric units and their derivatives is linked with regional specification. Here we show that patterning of the vertebrate hindbrain involves the direct upregulation of the chicken and pufferfish group 2 paralogous genes, Hoxb-2 and Hoxa-2, in rhombomeres 3 and 5 (r3 and r5) by the zinc finger gene Krox-20. We identified evolutionarily conserved r3/r5 enhancers that contain high affinity Krox-20. binding sites capable of mediating transactivation by Krox-20. In addition to conservation of binding sites critical for Krox-20 activity in the chicken Hoxa-2 and pufferfish Hoxb-2 genes, the r3/r5 enhancers are also characterized by the presence of a number of identical motifs likely to be involved in cooperative interactions with Krox-20 during the process of hindbrain patterning in vertebrates.